Curcumin Derivative Cur20 Attenuated Cerebral Ischemic Injury by Antioxidant Effect and HIF-1α/VEGF/TFEB-Activated Angiogenesis - Zhang, Runfang; Zhao, Tingkui; Zheng, Beibei; Zhang, Yun; Li, Xiaohui; Zhang, Feng; Cen, Juan; Duan, Shaofeng (Frontiers in Pharmacology, 2021)
In this paper, a curcumin derivative Cur20 was synthesized for better hydrolytic stability, which showed a higher angiogenic effect on zebrafish model than curcumin. In order to reveal the potential effects on neuroprotection, a mouse model of vascular dementia (VaD) induced by permanent right common carotid artery occlusion (rUCCAO) was established. After two weeks of curcumin administration, the cognitive function of mice was detected by Morris water maze and Y maze. The alteration on oxidative injuries and morphological damage were also analyzed by reactive oxygen species, superoxide dismutase, GSH, malondialdehyde tests, and Nissl stain on cortex/hippocampus. The angiogenesis and related signal factors were evaluated as well. The results showed that Cur20 significantly attenuated the cognitive dysfunction and histopathological changes of the VaD mice with enhanced antioxidant system and angiogenesis. In addition, primary rat brain microvessel endothelial cells (rBMECs) with oxygen glucose deprivation (OGD) were applied to further verify the possible mechanisms of Cur20-induced angiogenesis. The results demonstrated that the proliferation effect and the activation of pro-angiogenesis factors such as HIF-1α, VEGF, and TFEB might contribute to the protection of ischemic injury. Based on the above, our conclusion is that Cur20 can be considered as a promising therapeutic strategy for VaD.